Bread from stones the Middle East and the making of modern humanitarianism - Watenpaugh, Keith David 1966- (Univ. of California Press, 2015)
"Keith David Watenpaugh breaks new ground in analyzing the theory and practice of modern humanitarianism. Genocide and mass violence, human trafficking, and the forced displacement of millions in the early twentieth century Eastern Mediterranean form the background for this exploration of humanitarianism's role in the history of human rights. Watenpaugh's unique and provocative examination of humanitarian thought and action from a non-Western perspective goes beyond canonical descriptions of relief work and development projects. Employing a wide range of source materials...literary and artistic responses to violence, memoirs, and first-person accounts from victims, perpetrators, relief workers, and diplomats...Watenpaugh argues that the international answer to the inhumanity of World War I in the Middle East laid the foundation for modern humanitarianism and the specific ways humanitarian groups and international organizations help victims of war, care for trafficked children, and aid refugees."...Provided by publisher